Murder with mercy ebook - Heley, Veronica (Ellie Quicke, 2013)
Ellie Quicke is surrounded by problems on all sides – will she sink or swim? Ellie's friend on the police force asks her to enquire about some deaths in the community which might or might not be suicide, and various relatives of the deceased confirm their suspicions. Unbeknown to the police, an elderly lady moving in and out of dementia has come across some drugs and is using them to ease people in pain out of their misery. At the same time, the project to turn the quirky, turreted Pryce House into a hotel is dogged by problems and suspicion falls on the difficult twelve-year-old boy Mikey who Ellie has taken in. Social Services threaten to remove him into care. And Ellie's pregnant daughter Diana has been juggling problems caused by the slow convalescence of her estate agent husband. Can Ellie track down whoever it is who is killing for mercy, keep Mikey at home, and steer Diana into calmer waters?